Oral manifestations of COVID-19 and the role of the ACE2 receptor: what is known so far? - Luna-Mazzola, Ivo (2022)
COVID-19 is a currently pandemic disease that worries professionals in all areas of the Health Sciences. Current literature indicates that certain components of the stomatognathic system (such as lips, oral mucosa, tongue, and tonsils) express ACE2 receptors, responsible for the binding of SARS-CoV-2 to the human cell. This expression has a big impact on organular compromise, turning the oral cavity not only into an important route of viral entry but also into a region with the possibility of various manifestations such as xerostomia, halitosis, chemosensory alteration, opportunistic coinfection, and mucosal lesions. The fact that mouth manifestations are reported in the early stages of this disease suggests a possible predictive nature, which would make them very useful for diagnostic referral. In this sense, it is important that the dental professional knows how to recognize this early presentation symptomatology, being able to presumptively detect patients with COVID-19 in whom a significant systemic commitment has not yet been consolidated. This would allow the referral to medical consultation for definitive diagnostic purposes and, if correct, prevent both transmission and the advancement of the disease in the patient. Based on this important work, this review article synthesizes the scientific evidence published in the last 3 years (2019-2021 period) about the oral manifestations of COVID-19.